2017
DOI: 10.15448/1980-6108.2017.2.25208
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de medicamentos em crianças internadas em um hospital geral

Abstract: *** Medication use in children admitted to a general hospital ***AIMS: To describe the profile of medications used in children admitted to a general hospital.METHODS: A cross-sectional study was conducted with children aged 0 to 12 years, admitted to the Hospital Nossa Senhora da Conceição, in Tubarão, state of Santa Catarina, Brazil, between July 2013 and July 2014. The following data were collected: f age, sex, length of hospital stay, International Classification of Diseases codes for hospitalization, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…2 It is noteworthy that the metabolism related to the growth and development of children is differentiated from adults, altering the pharmacological action of the antibiotic, which requires rational use and careful attention in the storage, dispensing, prescription and administration to prevent further damages. 3 A study addressing the safety strategies in drug administration in children found that intravenous use was the most commonly used for this public in the hospital setting. 4 However, many children with infection begin parenteral antibiotic therapy in the hospital and complete the oral home therapy regimen.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is noteworthy that the metabolism related to the growth and development of children is differentiated from adults, altering the pharmacological action of the antibiotic, which requires rational use and careful attention in the storage, dispensing, prescription and administration to prevent further damages. 3 A study addressing the safety strategies in drug administration in children found that intravenous use was the most commonly used for this public in the hospital setting. 4 However, many children with infection begin parenteral antibiotic therapy in the hospital and complete the oral home therapy regimen.…”
Section: Introductionmentioning
confidence: 99%